SUBJECTIVITY AND BIOLOGY: AN ECOLOGICAL APPROACH - Maria da Silva, Berenice; Edjane da Silva Soares Guabira, Maria; José Brito da Silva, Maria; Gomes de Souza, Laudenice; Cândido Pereira, Edjanete; Maria da Silva, Josina; Berto Silva, Gledson; Edjanir Cândido Pereira, Maria; Margarete do Nascimento Mendonça, Maria; Holond de Lima Rocha, Kleyton (Revista Gênero e Interdisciplinaridade, 2023)
In this study, we aim to understand the motivation for teaching Biology, based on the meanings of subjectivity that attribute to a professional relationship and the motivation of its students. The text analyzes some transformations undergone by the notion of some preliminary results obtained through bibliographical research in the light of some authors. The results allow us to affirm that the subjective meanings that underlie motivation take on unique configurations depending on life stories and professional experiences. Such configurations are organized around central concerns, such as students’ meaningful learning, affective relationships with them and the scientific content taught. All aspects of teaching make sense within the teacher’s unique subjective configuration. Perceptions of competence materialize when it is used to think about the problem of the production of subjectivity.